2018
DOI: 10.1002/adma.201800316
|View full text |Cite
|
Sign up to set email alerts
|

Protein Toxin Chaperoned by LRP‐1‐Targeted Virus‐Mimicking Vesicles Induces High‐Efficiency Glioblastoma Therapy In Vivo

Abstract: Glioblastoma is a most intractable and high-mortality malignancy because of its extremely low drug accessibility resulting from the blood-brain barrier (BBB). Here, it is reported that angiopep-2-directed and redox-responsive virus-mimicking polymersomes (ANG-PS) (angiopep-2 is a peptide targeting to low-density lipoprotein receptor-related protein-1 (LRP-1)) can efficiently and selectively chaperone saporin (SAP), a highly potent natural protein toxin, to orthotopic human glioblastoma xenografts in nude mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 72 publications
4
96
0
Order By: Relevance
“…In line with our findings, Chu et al investigated the effect of Tet1 ligand density in neuronal cell uptake and concluded that lower densities of ligand resulted in improved internalization of HPMA-oligolysine copolymer NPs [241]. This could be explained by the fact that the excessive targeting ligand density can result in reduced selectivity, as steric hindrances can be formed due to the over proximity between ligands, decreasing their binding ability to neuronal cells and enhancing the binding to non-targeted cells [242]. Hence, it is important to optimize the NPs' ligand density to enhance targeting efficiency.…”
Section: Targeting Ligands Dilemmas In Neurospecific Deliverysupporting
confidence: 89%
“…In line with our findings, Chu et al investigated the effect of Tet1 ligand density in neuronal cell uptake and concluded that lower densities of ligand resulted in improved internalization of HPMA-oligolysine copolymer NPs [241]. This could be explained by the fact that the excessive targeting ligand density can result in reduced selectivity, as steric hindrances can be formed due to the over proximity between ligands, decreasing their binding ability to neuronal cells and enhancing the binding to non-targeted cells [242]. Hence, it is important to optimize the NPs' ligand density to enhance targeting efficiency.…”
Section: Targeting Ligands Dilemmas In Neurospecific Deliverysupporting
confidence: 89%
“…These approaches can be categorized into the following two strategies: tight junction disruption and active passage through the vascular wall by targeting biomarkers expressed on brain endothelial cells. Several ligands have been reported to bind with endothelial markers for crossing the BBB, for example, rabies virus glycoprotein (RVG) binds to the acetylcholine receptor (AchR), Tf peptide bind to TfRs,17b angiopep‐2 binds to low‐density lipoprotein receptor‐related protein‐1 (LRP‐1), and GLUT1 antibody scFv bind to GLUT1 …”
Section: Targeting Strategies With Ligand‐installed Nanocarriersmentioning
confidence: 99%
“…However, none of these methods were used for delivery of saporin-based constructs. The problem of BBB permeability for saporin-containing toxins was addressed in recent studies [146,147] where the authors used angiopep-2-directed and redox-responsive virus-mimicking polymersomes (angiopep-2 is a peptide targeting to low-density lipoprotein receptor-related protein-1) or apolipoprotein E peptide [(LRKLRKRLL)2C], which specifically binds to low-density lipoprotein receptor members. It was shown that these two approaches can efficiently and selectively chaperone saporin to orthotopic human glioblastoma xenografts in nude mice after systemic administration.…”
Section: Discussionmentioning
confidence: 99%